Primary Breadwinner Wives and Muslim Family Welfare: A Maqasid Framework - Nurul Putri Nafa; Widiya Yul (International Journal of Multidisciplinary Research of Higher Education, 2026)
The phenomenon of wives serving as primary breadwinners has become increasingly prevalent in Muslim families due to socio-economic changes and shifting gender roles. Previous studies have generally examined this issue from legal, economic, or gender perspectives separately, while comprehensive analyses based on Maqasid al-Shariah remain limited. This article employs a qualitative method using content analysis. The data consist of scholarly literature on Islamic family law, gender studies, family well-being, and contemporary Maqasid al-Shariah discourse, which were analyzed to examine the role of wives as primary breadwinners and to formulate a conceptual model of Muslim family well-being based on Maqasid al-Shariah. The data were analyzed using content analysis through the five dimensions of Maqasid al-Shariah: protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), progeny (hifz al-nasl), and wealth (hifz al-mal). The findings indicate that wives’ economic contributions can strengthen family resilience and well-being, while also creating challenges such as double burdens, psychosocial pressures, and patriarchal resistance Wives as primary breadwinners can be recognized as a legitimate form of social adaptation within Muslim families, aligning with the objectives of Maqasid al-Shariah when balance across its five dimensions is sustained; the proposed multidimensional model thus offers practical guidance for strengthening family policy, empowerment initiatives, and household resilience.